Hakikat Manusia Dalam Pandangan Buddhism Dan Relevansinya Dengan Konsep Dualisme Plato - wardani, Niken Wardani (PATISAMBHIDA : Jurnal Pemikiran Buddha dan Filsafat Agama, 2025)
PHow does Buddhism analyze human nature, and how does Plato's teaching on "dualism" explain the essence of man. The new researcher intends to describe human nature from the point of view of Buddhism and Plato's teaching on dualism, and its relevance. This study uses a quantitative method with a library research approach. Palto's teaching kicked man as duality, a human being consisting of two elements whose unity was not stated. The existence of the body is only limited to helping the soul achieve immortality. But Plato did not go into detail about the path to immortality. The Buddhist view is paramatthasacca (true truth), the human mind and body are the unity of nama and rupa (mind and body). The highest goal of the mind is Nibbana. Attempt to attain Nibbana by means of vipassana bhavana meditation, contemplation of mind and body. The harmony between mind and body is a major factor. Plato's opinion on "pre-existence" is in harmony with the concepts of kamma and punarbhava. The law of kamma is that what is done will bring results according to that action in the future. The law of Punarbhava is that humans who are still bound by lobha (greed), sin (hatred), and moha (ignorance) will experience birth and death in the universe. The relevance to the concept of "pre-existence" is that the mind (citta / consciousness) in this life already exists or has lived in a previous life.